2014
DOI: 10.1158/1538-7445.pedcan-b18
|View full text |Cite
|
Sign up to set email alerts
|

Abstract B18: Presence of tumor-associated macrophages in SHH medulloblastoma

Abstract: The concept of tumor-promoting inflammation is a recognized enabling characteristic of cancer. Tumor associated macrophages (TAMs), one of the main contributors to the tumor microenvironment, have been identified in many adult malignancies and in the MYCN non-amplified high risk neuroblastomas. TAMs have been shown to promote cancer via multiple mechanisms including tumor cell growth and survival, invasion, metastasis, angiogenesis, inflammation, and immune regulation. Recent studies in adult gliomas have demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, C3a-C3aR signaling in microglia contributes to β-amyloid pathology and neuroinflammation in Alzheimer's disease [55]; and this signaling in microglia was recently reported to drive the pathogenesis of neuromyelitis optica [56]. Meanwhile, microglia/macrophages were demonstrated to participate in MB TME [57], although the conclusions are paradoxical that Maxmov et al found tumor-associated macrophages impair MB growth [58], whereas Yao et al demonstrated microglia promotes MB progression through IGF1 production [59]. In our study, the ideal approach to exclude C3a's effect on microglia/macrophages during MB development is to conditionally knockout C3aR in astrocytes of MB mice, that means to generate transgenic mice by crossmating GFAP-cre and C3aR loxp/loxp mice, then to crossmate these mice with MB mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, C3a-C3aR signaling in microglia contributes to β-amyloid pathology and neuroinflammation in Alzheimer's disease [55]; and this signaling in microglia was recently reported to drive the pathogenesis of neuromyelitis optica [56]. Meanwhile, microglia/macrophages were demonstrated to participate in MB TME [57], although the conclusions are paradoxical that Maxmov et al found tumor-associated macrophages impair MB growth [58], whereas Yao et al demonstrated microglia promotes MB progression through IGF1 production [59]. In our study, the ideal approach to exclude C3a's effect on microglia/macrophages during MB development is to conditionally knockout C3aR in astrocytes of MB mice, that means to generate transgenic mice by crossmating GFAP-cre and C3aR loxp/loxp mice, then to crossmate these mice with MB mice.…”
Section: Discussionmentioning
confidence: 99%